2017
DOI: 10.7150/thno.21662
|View full text |Cite
|
Sign up to set email alerts
|

The cytotoxic effects of dimethyl sulfoxide in mouse preimplantation embryos: a mechanistic study

Abstract: Rationale: Dimethyl sulfoxide (DMSO) is commonly used as a solvent for water-insoluble substances, a vehicle for drug therapy, and a cryoprotectant for cultured cells. DMSO induced embryonic defects and its mechanism of action remains unclear. The rationale is based on the assumption that DMSO supplementation should induce long-term negative effects on both pre- and post-implantation embryo development.Methods: DMSO induced oxidative stress, ER stress, autophagy, mitophagy, signaling responsible genes and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 79 publications
1
52
1
1
Order By: Relevance
“…Chemical additives such as dimethyl sulfoxide (DMSO) and sodium butyrate (NaBu), which have been used for enhancing mAb production in rCHO cell cultures, may also activate ER stress. DMSO has been observed to induce ER stress in mouse embryonic cells . When cells are exposed to ER stress, an unfolded protein response (UPR) is activated to restore stress or to adapt to stress conditions in order to maintain homeostasis and cellular function .…”
Section: Introductionmentioning
confidence: 99%
“…Chemical additives such as dimethyl sulfoxide (DMSO) and sodium butyrate (NaBu), which have been used for enhancing mAb production in rCHO cell cultures, may also activate ER stress. DMSO has been observed to induce ER stress in mouse embryonic cells . When cells are exposed to ER stress, an unfolded protein response (UPR) is activated to restore stress or to adapt to stress conditions in order to maintain homeostasis and cellular function .…”
Section: Introductionmentioning
confidence: 99%
“…However, DMSO may have side effects on cell culture that are usually overlooked. For example, it has already been shown that DMSO can affect cell cycle [ 6 10 ], mitochondrial function [ 5 , 11 ], and the epigenetic landscape of various cell types [ 12 14 ]. More importantly, DMSO can prime the differentiation of various types of stem cells [ 7 , 15 18 ], and it is able to sustain mESC culture pluripotency in the absence of LIF [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, DMSO is also a hydrogen-bound disrupter, an intercellular electrical uncoupler, and a hydroxyl radical scavenger, among other properties [ 1 , 3 ], and could conceivably affect cell culture, depending on the cell type and the concentration used, issues that are usually overlooked. For instance, it has already been shown that apart from inducing cytotoxicity [ 4 6 ], DMSO can affect cell cycle [ 6 10 ] and mitochondrial function [ 5 , 11 ], as well as the epigenetic landscape of different cell types [ 12 14 ], and influence the differentiation of various types of stem cells [ 7 , 15 18 ]. Indeed, in 2012, Pal and colleagues reported that when exposing differentiating human embryonic stem cells (hESCs) to three different concentrations of DMSO, there was a dose-dependent downregulation of pluripotency markers and that the lowest concentration biased the differentiation process by enhancing mesodermal differentiation [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Modern data show that even in low concen-trationstheCPAsaffectsomaticandreproductive cells [8][9][10]. In this regard, the question of the CPAs influen ceonmetabolicprocessesincellsandtissues is getting relevant, especially in view of the development of such areas in medicine as cell and tissue therapy as well as assisted reproductive technologies [8][9][10].…”
mentioning
confidence: 99%
“…Modern data show that even in low concen-trationstheCPAsaffectsomaticandreproductive cells [8][9][10]. In this regard, the question of the CPAs influen ceonmetabolicprocessesincellsandtissues is getting relevant, especially in view of the development of such areas in medicine as cell and tissue therapy as well as assisted reproductive technologies [8][9][10]. Moreover, recently many authors have demanded the re-considering of using the CPAs in reproductive technologies, as modern experimental results demonstrate that CPAs within a wide range ofconcentrationshaveatoxiceffectatthegenome level, which leads to irreversible impairments in structure and functions of cells [8][9][10].…”
mentioning
confidence: 99%